Issues, problems and strategies of waqf land development in Malaysia literature review - Mokhtar, Salbiah; Ibrahim, Mansor; Omer, Spahic (2008)
Waqf is an Islamic concept of trust when an owner donates a land or property for a specific or general welfare of Muslim community. The prominent issues to confront is the abandonment and undeveloped of waqf land. The development of wagf land in Malaysia is limited to the provision of mosque, cemetery, surau and religious school. This has hindered waqf property from generating income that can benefit the Muslim society in this country. Therefore, there is a need to establish a new approach and strategy in creating an administrative system that is innovative, efficient and reflective to the current situation of economic development in Malaysia. This change is essential to guarantee the successful management of wagf land that will contribute to the enhancement of ummah's socia-economy. This achievement will alter the perception of the society about the traditional waqf practices. This paper will highlight the issues, challenges and strategies related to the waqf land especially the trustee in administering, managing and developing the waqf land. This paper also underlines the potential embrace by the waqf land if it is developed to its best and highest use according to the waqf law.